La question des objets médiatiques illégitimes et populaires - Virginie Spies (Mise au Point)
Television programs with mass appeal as well as gossip magazines are media objects that are often qualified as lower class or even as non-legitimate. This paper proposes to examine the position of the researcher, his constraints and his methods when he chooses to work on the discourse of media with a high audience and a bad image in the collective imagination. How can media discourse which is having a difficult time finding a legitimate place be understood in the realm of research? Finally, the question is to know if (as in the case of reality shows) a genre with mass appeal is doomed to disappear before becoming part of the history of television.